STRATEGI PENDIDIKAN ISLAM DI ERA MODERNISASI: INTEGRASI NILAI-NILAI KEISLAMAN DENGAN KETERAMPILAN ABAD 21 DAN TEKNOLOGI - Septia, Rizka; Bedi, Fisman; Fitri, Tin Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Islamic education in the modernization era faces complex challenges, especially in preserving Islamic values while adapting to advancements in science and technology. This study aims to identify effective strategies for Islamic education to remain relevant and adaptable amid modernization demands. Using a literature review method, this research analyzes recent literature on ideological challenges, the integration of religious and modern sciences, the utilization of technology, and learning models based on blended learning and Project-Based Learning. The findings indicate that Islamic education can benefit from a holistic approach that combines Islamic values with 21st-century skills and digital technology to enhance accessibility and learning interest. These findings contribute to the development of an Islamic education model that can shape a competent Muslim generation rooted in Islamic values. This study offers an innovative approach to curriculum development and the use of digital technology to support the goals of Islamic education in the globalization era.